Trajectories of cardio‐metabolic health in successful aging. (29th April 2019) - Dela, Flemming; Finkenzeller, Thomas; Ingersen, Arthur; Pötzelsberger, Birgit; Müller, Erich
Abstract : Maximal oxygen uptake (V̇O2max ) and muscle mass decrease with age. The loss of cardiorespiratory fitness and muscle strength is accelerated with physical inactivity and has well‐documented consequences for morbidity and all‐cause mortality. Participation in exercise training programs will improve one or more of the cardio‐metabolic risk factors, but the long‐term effects of such programs are questionable. Here, we re‐examined 25 old (72 ± 4 years.) men and women who considered him/herself as "success‐full agers" and were participants in a 3‐month alpine skiing training program 6 years earlier. The program focused on healthy aging and included health questionnaires, measurement of lipids and glycemic parameters in blood and a VO2max test. Thirteen and 12 subjects were in the intervention (IG) and the control group (CG), respectively. In response to the training program, subjects improved their cardio‐metabolic risk factors. However, after 6 years all positive effects had disappeared. Approximately 80% of the subjects had total cholesterol and LDL cholesterol above and HDL cholesterol below the recommended values, but these subjects remained the most metabolically deteriorated, including an increase in fasting glucose concentrations. We conclude that people seem to follow their individual trajectory in terms of cardio‐metabolic risk factors, and participation in a relatively short lasting exercise training program with emphasis on healthy aging does not change that. Long‐lasting change in lifestyle probably requires a continued attentional focus, goal setting, and feedback.